Characteristics of suicide in the city of Niš within the period 2000–2010 - Ljušić, Dragana; Ravanić, Dragan; Stojanović Tasić, Mirjana; Filipović Danić, Snežana; Cvetković, Jovana; Soldatović, Ivan (Vojnosanitetski pregled, 2020)
Background/Aim. Suicide is a significant public health problem worldwide. Numerous factors contribute to suicide. The aim of this study was to investigate the characteristics of suicide in the city of Niš in the period 2001–2010. Methods. The retrospective study consisted of 608 persons divided into three groups: suicide committers with mental disorders, somatic disorders or without registered disorders. Data on socio-demographic characteristics, previous suicide attempts, methods of suicide and presuicidal syndrome were obtained from the Police Directorate for the city of Niš, Ministry of Internal Affairs, Republic of Serbia and from the Statistical Office of the Republic of Serbia. Results. Persons with mental disorders were the most prevalent group of people who committed suicide (54.3%), followed by persons without registered disorders (31.9%) and with somatic disorders (13.8%). Persons with mental disorders who committed suicide were most often divorced, with high school education, monthly salary and with at least one previous suicide attempt. The hanging was the most frequent method of committing suicide in all investigated groups, followed by self-poisoning using drugs or liquid substances. The presuicidal syndrome was significantly more frequent among persons with mental disorders compared to persons with somatic disorders or without registered disorders others (45.8% vs. 16.7%, and 45.8% vs. 28.4% respectively p < 0.001). Conclusion. Although the persons with mental disorders are in the greatest risk of suicide, they are under medical care. In this regard, the prevention programs should be directed towards persons with severe somatic disorders and to old persons without registered disorders.
Keywords: suicide; risk factors; comorbidity; mental disorders; psychophysiologic disorders; serbia.